2015
DOI: 10.1093/protein/gzv001
|View full text |Cite
|
Sign up to set email alerts
|

Improving thermal and detergent stability of Bacillus stearothermophilus neopullulanase by rational enzyme design

Abstract: Neopullulanase, a glycosyl hydrolase from Bacillus stearothermophilus (bsNpl), is a potentially valuable enzyme for starch and detergent industries. However, as the protein is not active at elevated temperatures and high surfactant concentrations, we aimed to increase its stability by rational enzyme design. Nine potentially destabilizing cavities were identified in the crystal structure of the enzyme. Based on computational predictions, these cavities were filled by residues with bulkier side chains. The five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…(5) pullulanase type II (amylopullulanase) attacks α-1,6 linkages in pullulan and branched substrates in addition to α-1,4 links in polysaccharides other than pullulan (Bertoldo and . . Duffner et al, 2002). Pullulanases belong to group of glycosylhydrolases that are widely distributed in nature and are produced by an extremely wide variety of species such as animals, plants and microorganisms (Hyun and Zeikus, 1985;Zhang et al, 2013;Duan and Wu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(5) pullulanase type II (amylopullulanase) attacks α-1,6 linkages in pullulan and branched substrates in addition to α-1,4 links in polysaccharides other than pullulan (Bertoldo and . . Duffner et al, 2002). Pullulanases belong to group of glycosylhydrolases that are widely distributed in nature and are produced by an extremely wide variety of species such as animals, plants and microorganisms (Hyun and Zeikus, 1985;Zhang et al, 2013;Duan and Wu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From R8 onwards, selection was based on more than one property and only a small subset of variants was thoroughly characterized, making the task of assigning a role to specific changes more difficult. For example, it has been suggested that surfactant stability correlates with thermal stability (Ece et al 2015;Salameh and Wiegel 2010). In this study, the SDS stability increased as evolution progressed, but the same cannot be said for thermos-stability.…”
Section: Sequence Analysismentioning
confidence: 59%
“…This approach is labour intensive and assumes that the changes will not degrade the activity of the enzyme. Finally, previous studies (Ece et al 2015) have shown that increased thermal stability can give rise to increased tolerance to surface active agents, but evolution with selection for tolerance to surface active agents has not been described in the literature. Overall, we expected that directed evolution would be a more efficient way to generate tolerance to both proteases and surface active agents.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
“…The stability of microbial rhodopsins was tested by considering several factors, including temperature, pH, detergent, high salt concentration, and dehydration. This stable protein was extracted from microorganisms living in extreme environments ( Ece et al., 2015 ; Ji et al., 2017 ; Otzen, 2002 ; Shionoya et al., 2018 ), and the results led to continued research on various applications such as biochips and biosensors, as well as optogenetic tools ( Li et al., 2018 ). In this study, we investigated Tara76 rhodopsin, which exhibits stability against temperature, detergent, pH, salt, and dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proteins reported to be stable for several factors are generally not stable under all stressful conditions. Therefore, the stability of complex and specific factors must be improved for industrial and academic applications ( Ece et al., 2015 ; Foit et al., 2009 ; Magliery, 2015 ; Otzen, 2002 ). Mutagenesis may also be used to improve stability ( Foit et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%